WO3-ZIFs composite film for photoelectric cathode protection and application of WO3-ZIFs composite film

By constructing the WO3-ZIFs composite film, using hydrothermal method and electrodeposition technology, the problem of low energy storage efficiency and poor stability of photocathode protection technology in dark conditions is solved, and efficient protection of metals in light/dark states is achieved.

CN119824424APending Publication Date: 2025-04-15HENAN ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889213.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing photocathode protection technology has low energy storage efficiency and poor stability in dark conditions, making it difficult to effectively protect metals in light/dark states.

Method used

Using WO3-ZIFs composite film, WO3 films were grown by hydrothermal method and ZIFs were introduced through electrodeposition technology to construct a heterostructure with built-in electric field and regulate the ligand type to improve hydrophobicity.

Benefits of technology

It realizes efficient photogenerated electrons and hole separation, improves energy storage efficiency and stability, and provides stable protection for metals in light/dark states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824424A_ABST
    Figure CN119824424A_ABST
Patent Text Reader

Abstract

The invention discloses a WO3-ZIFs composite film for photoelectric cathode protection and application of the WO3-ZIFs composite film, and belongs to the technical field of corrosion protection. The WO3-ZIFs composite film is prepared by a preparation method comprising the following steps: cleaning conductive glass; growing a WO3 thin film on the conductive glass obtained in the step (1) through a hydrothermal method; the WO3-ZIFs composite film for photoelectric cathode protection is obtained on the surface of the WO3 film through an electro-deposition technology. The WO3-ZIFs energy storage photoanode with controllable hydrophobicity is constructed, the problems of low dark state energy storage efficiency, high electron and hole recombination rate, weak photoanode stability and the like of a WO3-based photoanode are solved through a strategy of changing ligand types and constructing heterostructure synergy, and stable protection on metal in a bright / dark state is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion protection, and in particular to a WO3-ZIFs composite film for photoelectric cathode protection and application thereof. Background Art

[0002] Cathodic protection technology is widely used in corrosion protection of marine infrastructure due to its advantages of being direct, thorough and durable. At present, the commonly used cathodic protection methods are mainly divided into two categories: sacrificial anode cathodic protection and impressed current cathodic protection. For sacrificial anode cathodic protection technology, this technology not only has the disadvantages of "energy consumption in the production process" and "dissolved products are easy to pollute the marine ecological environment", but also has the disadvantage that the protection efficiency is limited by the decomposition rate and shedding process of the anode material. For impressed current cathodic protection technology, this technology has the disadvantages of "high detection and maintenance costs", "requires a continuous and stable power supply" and "a large amount of resource costs and manpower costs are required to lay power transmission pipelines in coastal islands and reefs". Therefore, it is imperative to develop new cathodic protection technologies with green and environmental advantages.

[0003] Photocathode protection technology is a new type of cathodic protection technology that uses inexhaustible solar energy to protect metals from corrosion. It has the technical advantages of directness and thoroughness of cathodic protection technology, while avoiding the disadvantages of traditional cathodic protection technology in polluting the environment and consuming resources, which has attracted widespread attention from scientific researchers. Its principle is that when an n-type semiconductor is excited by incident light, the valence band electrons are excited to the conduction band, forming the separation of photogenerated electrons and holes. If the potential of photogenerated electrons is more negative than the self-corrosion potential of the metal, they can be transferred to the metal that forms an electrical connection with it and enriched on the surface of the metal, thereby achieving cathodic protection of the metal. Intermittency and regionality are a major problem in the field of optoelectronic applications. When it is dark, dark, and rainy, metal components in the ocean face more severe corrosion environments and problems such as the inability to perform immediate maintenance by humans. Photocathode protection technology can hardly play its corrosion protection role at this time.

[0004] WO3 is regarded as a photoanode with great potential for energy storage due to its high electron mobility, low cost, and environmental friendliness. x WO3 stores electrons. Under dark conditions, the stored electrons are released and M x WO3 is converted to WO3. However, the higher recombination rate of electrons and holes in WO3 makes it show lower dark state energy storage efficiency and dark state photocathode protection performance. Constructing heterostructures with built-in electric fields is considered an effective measure to improve the efficiency of semiconductor photoelectric separation. ZIFs materials have attracted widespread attention in the field of photocathode protection due to their high specific surface area, easy to adjust structure and wide light absorption range. Summary of the invention

[0005] The present invention provides a WO3-ZIFs composite film for photocathode protection and its application, which solves the problems of low energy storage efficiency and poor stability in the existing photocathode protection technology. WO3 and ZIFs have good energy band matching, and the constructed heterostructure promotes the effective separation of photogenerated electrons and holes, thereby achieving a higher energy storage efficiency. At the same time, by regulating the type of ligand, the effective regulation of its surface hydrophobicity is achieved, which not only effectively improves the stability of the photoanode, but also provides a good reference idea for the construction of a solar panel with both hydrophobicity and energy storage functions.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] The present invention provides a WO3-ZIFs composite film for photoelectric cathode protection, which is prepared by the following preparation method:

[0008] (1) Cleaning the conductive glass;

[0009] (2) growing a WO3 thin film on the conductive glass treated in step (1) by a hydrothermal method;

[0010] (3) A WO3-ZIFs composite film for photocathode protection is obtained by electrodeposition technology on the surface of the WO3 film.

[0011] Wherein, in step (1), the cleaning is specifically to place the conductive glass in a first solution and a second solution for ultrasonic cleaning; the first solution is ethanol or acetone, and the second solution is deionized water; the time of each ultrasonic cleaning is 10 to 30 minutes.

[0012] Wherein, the conductive glass is FTO conductive glass or ITO conductive glass.

[0013] Among them, step (2) is specifically as follows: dissolving 5-10g of sodium tungstate in 60ml of water or anhydrous ethanol, then adding 5-10ml of concentrated sulfuric acid to make a mixed solution, then placing the cleaned conductive glass in the above mixed solution, reacting at 90-110°C for 7-9h, then transferring to a muffle furnace and heating to 400-600°C, calcining for 1-3h to obtain a WO3 film.

[0014] Wherein, the added amount of the concentrated sulfuric acid is 7 ml.

[0015] Among them, step (3) is specifically as follows: using conductive glass covered with WO3 as the working electrode, Pt and saturated calomel as the counter electrode and reference electrode respectively, using 50ml of 0.15M Co(NO3)2·6H2O solution as the electrolyte, at a voltage of -1.0V (vs SCE) for 200s to prepare Co(OH)2 on the WO3 surface; soaking the above samples in 1M 2-methylimidazole solution, 1M benzimidazole solution, and 1M 5-chlorobenzimidazole solution for 12h, respectively, and vacuum drying at 80℃ for 1h to obtain WO3-ZIF-1, WO3-ZIF-2 and WO3-ZIF-3.

[0016] The invention also provides an application of a WO3-ZIFs composite film in photoelectric cathode protection.

[0017] In order to achieve effective protection of metals under dark conditions, this work constructed a WO3-ZIFs energy storage photoanode with controllable hydrophobicity. This material has the following advantages: 1) The large specific surface area and porosity of ZIFs can provide more active sites, thereby improving the efficiency of light utilization of the composite photoanode; 2) The conduction band potential of ZIFs is significantly lower than that of WO3. The built-in electric field constructed by the two is conducive to promoting the separation of photogenerated electrons and holes and improving the photoelectric conversion efficiency; 3) The hydrophobicity of the WO3-ZIFs photoanode can be effectively controlled by regulating the ligand type of ZIFs; 4) The WO3 nanosheets modified with ZIFs exhibit good hydrophobicity, which can not only reduce the wetting and erosion of the solution on the photoanode and improve the stability of the photoanode, but also reduce the light transmittance and thus improve the light utilization efficiency.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention constructs a WO3-ZIFs energy storage photoanode with controllable hydrophobicity. By changing the ligand type and constructing a heterostructure synergistic strategy, the low dark state energy storage efficiency, high electron and hole recombination rate and weak photoanode stability of the WO3-based photoanode are solved, and stable protection of metals in the light / dark state is achieved. It should be noted that the composite photoanode prepared by the present invention can achieve stable light / dark state photoelectrochemical cathodic protection of 304SS in a seawater environment without a hole capture agent.

[0020] 2. The preparation method of the WO3-ZIFs composite film of the present invention solves the problems of complicated and inefficient preparation process of the current photoanode. The present invention successfully obtains a WO3-ZIFs film with dual functions of hydrophobicity and energy storage by in-situ growth of WO3 on the surface of conductive glass and introduction of ZIFs by electrodeposition technology. The preparation method of the film has the advantages of being simple, efficient, and easy to mass produce, and the prepared photoanode has high stability and corrosion protection efficiency.

[0021] 3. The WO3-ZIFs energy storage photoanode prepared by the present invention has the advantages of high specific surface area, good hydrophobicity and high dark state energy storage efficiency. It can not only be used in the field of photocathode protection, but also has important reference significance for the preparation of self-cleaning solar panels with high hydrophobicity and energy storage efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0023] Figure 1 is the XRD pattern of WO3-ZIFs;

[0024] Figure 2 The hydrophobic performance diagram of WO3-ZIFs;

[0025] Figure 3 This is the UV-visible spectrum of WO3-ZIFs;

[0026] Figure 4 The photoinduced open circuit short-term potential change diagram of WO3-ZIFs in the absence of hole trapping agent and intermittent light;

[0027] Figure 5 Scanning electron microscope images of WO3-ZIFs (a is WO3, b is WO3-ZIF-1). DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a WO3-ZIFs composite film for photocathode protection, which is prepared by the following preparation method:

[0031] (1) The FTO conductive glass was ultrasonically cleaned in ethanol for 20 min, and then ultrasonically cleaned in deionized water for 20 min;

[0032] (2) Dissolve 6.9 sodium tungstate in 60 ml of water, then add 7 ml of concentrated sulfuric acid to make a mixed solution, then place the cleaned FTO conductive glass in the mixed solution, react at 100 ° C for 8 hours, then transfer to a muffle furnace and heat to 500 ° C, calcined for 2 hours, and obtain a WO3 film;

[0033] (3) FTO conductive glass covered with WO3 was used as the working electrode, Pt and saturated calomel were used as the counter electrode and reference electrode, respectively. 50 ml of 0.15 M Co(NO3)2·6H2O solution was used as the electrolyte. At a voltage of -1.0 V (vs SCE) for 200 s, Co(OH)2 was prepared on the WO3 surface. The above samples were immersed in 1 M 2-methylimidazole solution, 1 M benzimidazole solution, and 1 M 5-chlorobenzimidazole solution for 12 h, respectively, and dried at 80 °C under vacuum for 1 h to obtain WO3-ZIF-1, WO3-ZIF-2, and WO3-ZIF-3.

[0034] Example 2

[0035] This embodiment provides a WO3-ZIFs composite film for photocathode protection, which is prepared by the following preparation method:

[0036] (1) The ITO conductive glass was ultrasonically cleaned in acetone for 10 min, and then ultrasonically cleaned in deionized water for 30 min;

[0037] (2) Dissolve 5g of sodium tungstate in 60ml of anhydrous ethanol, then add 5ml of concentrated sulfuric acid to make a mixed solution, then place the cleaned ITO conductive glass in the mixed solution, react at 90°C for 9h, then transfer to a muffle furnace and heat to 400°C, calcining for 3h to obtain a WO3 film;

[0038] (3) Conductive glass covered with WO3 was used as the working electrode, Pt and saturated calomel were used as the counter electrode and reference electrode, respectively. 50 ml of 0.15 M Co(NO3)2·6H2O solution was used as the electrolyte. At a voltage of -1.0 V (vs SCE) for 200 s, Co(OH)2 was prepared on the WO3 surface. The above samples were immersed in 1 M 2-methylimidazole solution, 1 M benzimidazole solution, and 1 M 5-chlorobenzimidazole solution for 12 h, respectively, and dried at 80 °C under vacuum for 1 h to obtain WO3-ZIF-1, WO3-ZIF-2, and WO3-ZIF-3.

[0039] Example 3

[0040] This embodiment provides a WO3-ZIFs composite film for photocathode protection, which is prepared by the following preparation method:

[0041] (1) The FTO conductive glass was ultrasonically cleaned in ethanol for 30 min, and then ultrasonically cleaned in deionized water for 10 min;

[0042] (2) Dissolve 10g of sodium tungstate in 60ml of anhydrous ethanol, then add 10ml of concentrated sulfuric acid to make a mixed solution, then place the cleaned conductive glass in the mixed solution, react at 110°C for 7h, then transfer to a muffle furnace and heat to 600°C, calcining for 1h to obtain a WO3 film;

[0043] (3) Conductive glass covered with WO3 was used as the working electrode, Pt and saturated calomel were used as the counter electrode and reference electrode, respectively. 50 ml of 0.15 M Co(NO3)2·6H2O solution was used as the electrolyte. At a voltage of -1.0 V (vs SCE) for 200 s, Co(OH)2 was prepared on the WO3 surface. The above samples were immersed in 1 M 2-methylimidazole solution, 1 M benzimidazole solution, and 1 M 5-chlorobenzimidazole solution for 12 h, respectively, and dried at 80 °C under vacuum for 1 h to obtain WO3-ZIF-1, WO3-ZIF-2, and WO3-ZIF-3.

[0044] Experimental Example 1 The phase composition of the WO3-ZIFs composite film was tested by XRD using an X-ray diffractometer (model: BRUCKER D8 ADVANCE).

[0045] The target material used in the test is Cu target, the test angle range is 10-80°, and the grazing test mode is adopted. Figure 1 As shown in the XRD spectrum, the diffraction peaks at 23.1°, 23.6°, 24.31°, 26.5°, 28.8°, 34.1°, 41.9°, and 49.9° correspond to the (002), (020), (200), (120), (112), (202), (222), and (223) crystal planes of WO3, respectively, indicating the successful preparation of WO3. Relative to WO3, the diffraction peaks of ZIFs at 10.4°, 12.8°, 18.1°, and 19.3° confirm the successful preparation of WO3-ZIFs composite films.

[0046] Experimental Example 2: The contact angle between a water droplet and the coating surface was measured using an optical contact angle meter to explore the effects of different ligand types on the hydrophobic properties of WO3-ZIFs photoanode. The specific steps are: drop a 2μL water droplet on the coating surface and measure the static contact angle of the water droplet after stabilization.

[0047] like Figure 2As shown, the contact angles of WO3, WO3-ZIF-1, WO3-ZIF-2 and WO3-ZIF-3 are 11°, 66°, 139.3° and 141.7°, respectively, indicating that the surface hydrophobicity of WO3-ZIFs can be effectively regulated by regulating the ligand type.

[0048] Experimental Example 3: The optical properties of WO3-ZIFs were tested by UV-visible spectroscopy to explore the effects of different ligand types on optical absorption. g =1240 / λ g ) calculated the band gaps of all WO3-ZIFs.

[0049] like Figure 3 As shown in the figure, the maximum light response wavelength of WO3 is 475nm (2.6eV), and the maximum light response wavelengths of WO3-ZIF-1, WO3-ZIF-2 and WO3-ZIF-3 are basically in the range of 650-675nm (1.8-1.9eV). The above phenomenon shows that WO3-ZIFs have a wider light absorption range, which helps to improve the utilization efficiency of sunlight.

[0050] Experimental Example 4: Photoelectrochemical cathodic protection effect test of WO3-ZIFs composite film

[0051] The open circuit potential of WO3-ZIFs composite film coupled with metal was used to explore the photocathodic protection performance of the material for 304SS. The test used a three-electrode method, with platinum as the counter electrode, Ag / AgCl as the reference electrode, 304SS coupled with WO3-ZIFs composite film as the working electrode, and 3.5wt% NaCl solution without hole capture agent as the electrolyte. The electrochemical workstation and light source system used in this test were Coster CS 350M electrochemical workstation and PLS-SXE300E respectively.

[0052] like Figure 4As shown in the figure, under illumination conditions, the coupling potential between WO3 and 304SS is about -0.14V (vs Ag / AgCl), which is positive to the self-corrosion potential of 304SS (-0.16V vsAg / AgCl). The above phenomenon shows that the high carrier recombination rate makes it difficult for WO3 to effectively protect 304SS. The coupling potentials of WO3-ZIFs and 304SS are all lower than the self-corrosion potential of 304SS, indicating that the above materials can effectively protect 304SS. Among them, WO3-ZIF-1 not only shows high protection performance, but also has high stability. The WO3-ZIF-1 composite film can polarize the potential of 304SS to -0.25V, and can provide 90mV photoelectrochemical cathodic protection for 304SS. At the same time, effective protection of 304SS can be achieved in both light and dark states. This phenomenon is attributed to the matching built-in electric field and suitable hydrophobicity of WO3-ZIFs. Specifically, the matching built-in electric field improves the transfer efficiency of photogenerated electrons and holes, and the appropriate hydrophobicity has the function of maintaining electrode stability and sufficient electrolyte infiltration. Therefore, WO3-ZIF-1 exhibits excellent light / dark state photocathode protection performance.

[0053] Experimental Example 5: The microscopic morphology of the WO3-ZIF-1 composite film was observed by a scanning electron microscope (model: German ZEISS Sigma 300) to further reveal the reason why WO3-ZIF-1 exhibits excellent photocathodic protection performance.

[0054] like Figure 5 As shown in a, WO3 presents a uniform nanosheet structure. In comparison, WO3-ZIF-1 contains nanosheet-like WO3 and rhombic dodecahedral ZIF-1 ( Figure 5 b) This phenomenon shows that WO3-ZIF-1 has a higher optical absorption area, which plays a significant role in improving the efficiency of light utilization.

[0055] It can be seen that the present invention obtains a series of WO3-ZIFs composite films for photocathode protection through a hydrothermal method and an electroplating method. The composite film delays the irradiation recombination of electrons and holes, significantly improving the photoelectric conversion efficiency. Compared with WO3, which cannot effectively protect 304SS, the WO3-ZIFs film with matching energy bands and suitable hydrophobicity can achieve stable light / dark state protection of 304SS in a seawater environment. The film acquisition method is simple and easy to obtain, low in cost, and more in line with the actual marine application environment (avoiding the drawbacks of adding hole capture agents), laying a foundation for the large-scale production and application of such materials.

[0056] In summary, the above experimental results all illustrate that the WO3-ZIFs composite film for photocathode protection of the present invention can provide effective light / dark state photocathode protection for 304SS and extend the service life of the metal.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A WO3-ZIFs composite film for photocathode protection, characterized in that Made by the following preparation method: (1) Cleaning the conductive glass; (2) growing a WO3 thin film on the conductive glass treated in step (1) by a hydrothermal method; (3) A WO3-ZIFs composite film for photocathode protection is obtained by electrodeposition technology on the surface of the WO3 film.

2. The WO3-ZIFs composite film for photocathode protection according to claim 1, characterized in that: In step (1), the cleaning is specifically performed by placing the conductive glass in a first solution and a second solution for ultrasonic cleaning; the first solution is ethanol or acetone, and the second solution is deionized water; the time for each ultrasonic cleaning is 10 to 30 minutes.

3. The WO3-ZIFs composite film for photocathode protection according to claim 1, characterized in that: The conductive glass is FTO conductive glass or ITO conductive glass.

4. The WO3-ZIFs composite film for photocathode protection according to claim 1, characterized in that: Step (2) is specifically as follows: dissolve 5-10g of sodium tungstate in 60ml of water or anhydrous ethanol, then add 5-10ml of concentrated sulfuric acid to make a mixed solution, then place the cleaned conductive glass in the mixed solution, react at 90-110°C for 7-9h, then transfer to a muffle furnace and heat to 400-600°C, calcining for 1-3h to obtain a WO3 film.

5. The WO3-ZIFs composite film for photocathode protection according to claim 4, characterized in that: The amount of concentrated sulfuric acid added is 7 ml.

6. The WO3-ZIFs composite film for photocathode protection according to claim 1, characterized in that: Step (3) is specifically as follows: using conductive glass covered with WO3 as the working electrode, Pt and saturated calomel as the counter electrode and reference electrode respectively, using 50ml of 0.15M Co(NO3)2·6H2O solution as the electrolyte, at a voltage of -1.0V (vs SCE) for 200s to prepare Co(OH)2 on the WO3 surface; soaking the above samples in 1M 2-methylimidazole solution, 1M benzimidazole solution, and 1M 5-chlorobenzimidazole solution for 12h, respectively, and vacuum drying at 80℃ for 1h to obtain WO3-ZIF-1, WO3-ZIF-2 and WO3-ZIF-3.

7. Use of the WO3-ZIFs composite film according to any one of claims 1 to 6 in photocathode protection.